Lights, Camera, Reaction: Evaluating Extent of Transformative Learning and Emotional Engagement Through Viewer-Responses to Environmental Films - Esmail, Shefaza; Matthews-Roper, Misty (Frontiers in Education, 2022)
In sustainability education affective responses to climate change are rarely discussed, and this is to the detriment of students. One way to address this gap in higher education for sustainability is learner-centred teaching using transformative learning principles. The processes for implementation may vary. Our preliminary study evaluated the contribution of environmental films paired with viewer-response activities, such as reflections and discussions, to create emotional engagement and facilitate transformative learning in an online course where content focused on sustainability and climate change. Data for the study were gathered through two questionnaires, student reflections, and interviews. Our study found that the process of film watching, reflection writing, and engaging in discussion was conducive to incorporating five of the six elements of transformative learning: individual experience, promoting critical reflection, awareness of context, dialogue, and authentic relationships. We conclude that films are an effective means of conveying complex content in an online course pertaining to climate change and sustainability. We propose pairing films with viewer-response strategies, especially reflections to allow students to identify their feelings, biases, and preconceived frames of references and stimulate the path toward transformative learning in higher education.